Proposal and validation of colour index for Kinnow mandarin (Citrus nobilis × Citrus deliciosa) - THAKRE, MADHUBALA; VERMA, M K; SINGH, KANHAIYA; AWASTHI, O P; SHARMA, R R; RAY, MRINMOY (The Indian Journal of Agricultural Sciences, 2018)
Kinnow (Citrus nobilis Lour × Citrus deliciosa Tenora) acceptability by consumer and processors depends on their bright orange colour, size and other quality traits like TSS and acidity. More bright orange coloured Kinnow fruits are preferred. The objective of this study is to propose an index for growers and researchers to know the harvesting date and better quality of fruits respectively. Kinnow fruits of varying colour gradient were harvested from ten treatments. These ten treatments were different doses of N: P: K. They acted as a source to produce variability in Kinnow peel colour, which was utilized for index formulation and validation. They were compared with a standard. Standard comprised of most uniform bright orange coloured fruits of Kinnow orange. The observations for L, a and b were recorded by Hunterlab. There were total eleven colour indexes studied. Out of eleven indexes, seven were previously validated by other workers for different fruit crops. Four indexes were formulated in this study to validate them for Kinnow along with remaining seven indexes. Index a/b showed highest positive correlation with total carotenoid content of peel (0.548 and 0.519 respectively). It recorded minimum value for standard (0.52±0.02) indicates that lower values for these indices will represent brighter colour of kinnow.